2019
DOI: 10.1038/s41598-019-46240-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute stress-induced change in polysialic acid levels mediated by sialidase in mouse brain

Abstract: Stress is an important environmental factor influencing human behaviour and causing several mental disorders. Alterations in the structure of polysialic acid (polySia/PSA) due to genetic alterations in ST8SIA2, which encodes a polySia-synthesizing enzyme, are related to certain mental disorders. However, whether stress as an environmental factor leads to changes in polySia structure is unknown. Here we studied the effects of acute stress on polySia expression and found reductions in both the quantity and quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 63 publications
4
19
0
Order By: Relevance
“…is particularly abundant in the brain, and regulates cell adhesion, synaptogenesis, memory, and neurogenesis, as well as binding neurotrophins, growth factors, and neurotransmitters (Sato and Kitajima, 2013;Colley et al, 2014). In mouse brain, polysialylation dramatically decreases 2 weeks after birth, and almost disappears by 8 weeks, except in olfactory bulb, hippocampus, amygdala, suprachiasmatic nucleus, and prefrontal cortex (Abe et al, 2019). Polysialylated NCAM is also present on the surface of microglia, and rapidly decreases in response to LPS activation as a result of the microglial release of sialidase, which then desialylates NCAM (Sumida et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…is particularly abundant in the brain, and regulates cell adhesion, synaptogenesis, memory, and neurogenesis, as well as binding neurotrophins, growth factors, and neurotransmitters (Sato and Kitajima, 2013;Colley et al, 2014). In mouse brain, polysialylation dramatically decreases 2 weeks after birth, and almost disappears by 8 weeks, except in olfactory bulb, hippocampus, amygdala, suprachiasmatic nucleus, and prefrontal cortex (Abe et al, 2019). Polysialylated NCAM is also present on the surface of microglia, and rapidly decreases in response to LPS activation as a result of the microglial release of sialidase, which then desialylates NCAM (Sumida et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, interestingly and most importantly, those SNPs are unambiguously demonstrated to bring about impairments of structures and functions of polySia, as far as evaluated by biochemical and functional analyses [ 1 , 19 , 26 , 27 , 33 , 34 , 46 ]. In addition, environmental factors that significantly increase the risk of pathogenesis of mental disorders also influence the expression profile of polySia–NCAM in a brain-region-specific manner [ 36 , 37 ]. Thus, both genetic and environmental factors of mental disorders greatly affect the structure and location of polySia–NCAM in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these studies, it was demonstrated that reported mutations or SNPs of ST8SIA2 showed impaired polySia in structures and functions [ 1 ]. Recently, not only genetic factors but also environmental factors, such as stress, have been found to change polySia expression in the brain region specifically [ 36 ]. In addition, chlorpromazine, an anti-psychotic medication, has also been found to change the polySia expression in the prefrontal cortex [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, environmental factors such as stress and medicine can alter polySia. Acute stress leads to reductions in both the quantity and quality of polySia in the olfactory bulb and prefrontal cortex [ 35 ], and treatment with anti-schizophrenia agents can consistently upregulate the expression of polySia in the PFC [ 36 ], a location in which altered polySia-NCAM expression has been observed in schizophrenia patients [ 37 ]. Taken together, these findings indicate that the quantity and quality of polySia are both highly controlled in the normal brain and in tissues.…”
Section: Introductionmentioning
confidence: 99%